Evaluasi Teknis dan Rekomendasi Perbaikan Prasarana Aksesibilitas pada Lingkungan Sekolah Luar Biasa : Studi Kasus: SLB -A (Tunanetra) Negeri 1 Bantul - Andi Al Muastagfir Syah; Ahsan Hidayat Setiadi; Nahdatunnisa Nahdatunnisa (Universitas Sulawesi Tenggara, 2026)
Accessibility infrastructure is a crucial component of special school facilities to ensure safety and independent mobility for students with visual impairments (students with visual disabilities / blind students). Although national regulations provide technical standards, many special school environments for visually impaired students still show inadequate technical performance, particularly in tactile paving systems, guiding blocks, ramps, corridors, and circulation paths. Previous studies mainly identify the availability of accessible facilities for visually impaired users, with limited focus on evaluating their technical performance under actual operational conditions. This study aims to evaluate the technical performance of accessibility infrastructure specifically for visually impaired students and to formulate improvement recommendations based on field conditions. A mixed-method approach with a technical evaluation emphasis was applied through measured observations, documentation, mobility simulations involving visually impaired users, and comparison with national accessibility standards (Regulation of the Ministry of Public Works and Housing No. 14/2017). The case study was conducted at SLB Negeri 1 Bantul. The expected outcomes include a technical performance profile of accessibility infrastructure for visually impaired students, identification of critical accessibility issues affecting blind and low-vision users, and practical technical recommendations to support infrastructure improvement in special schools.